Student satisfaction in virtual education - Yaneth Aleman Vilca; Paola Alarcon Saravia; Miguel Pacheco Quico; Ariosto Carita Choquecahua; Rildo Bellido Medina; Jose Calizaya Lopez (Universidad Ciencia y Tecnología, 2024)
Virtual education emerged as a response to the COVID-19 pandemic, allowing for educational continuity through social distancing. However, this transition revealed inequalities in access to and use of technology among students and teachers, influenced by factors such as geographical location, economic resources, and technology training. Additionally, the pandemic generated psychosocial issues that impacted students' emotional well-being, increasing stress and sleep disorders. Although various studies have analyzed virtual education, focusing on its behavior during and after the crisis, a significant gap has been observed between public and private education in terms of resources and quality. This study focuses on student satisfaction in virtual education, exploring conditions and methodological variables, and is part of a chapter in a book examining the educational system during the pandemic.